Bridging Research and Practice in Higher Technical Education - Kulkarni, P. D. (Journal of Engineering Education Transformations, 2010)
The task of bridging research and practice in Higher Technical Education requires an agenda that allows for the flow of information, ideas and research questions in both directions from researchers in education to practitioners of education.